Comparasional Speaking of INGKAR Boy Candra’s Novel on Indonesia Language Instructional: Febrianti Sulistiya, Jatut Yoga Prameswari, Ahmad Khoiril Anam - Febrianti Sulistiya; Jatut Yoga Prameswari; Ahmad Khoiril Anam (PT. Lancar Media Komunikasi, 2022)
The purpose of this study is to interpret the types of comparative figure of speech used in Boy Candra's novel “Ingkar” and their implications for learning Indonesian. This study uses a qualitative descriptive research method. This research as a whole utilizes interpretation in presenting data in descriptive form. The research method in this study uses documentation techniques. The instrument in this research is the researcher himself as a human instrument. The findings of comparative figure of speech in Boy Candra's novel Ingkar found 250 data with 68 sentences of comparative figure of speech, 27 sentences of metaphorical figure of speech, 62 sentences of personification figure of speech, 40 sentences of depersonification figure of speech, 12 sentences of allegorical figure of speech, 22 sentences of antithesis figure of speech , figure of speech pleonasm and tautology as many as 11 sentences, figure of speech periphrasis as many as 3 sentences, and figure of speech anticipation as much as 5 sentences. The dominant comparative figure of speech in Boy Candra's novel Ingkar , namely the comparison figure of speech for the category of parables as many as 68 sentences with a percentage. Key words: Figurative Language, Comparative Figure Of Speech, Refusing Novel, Indonesia language Instructional